(untitled) (Tokyo, 1962)
This book is a selection of graded readings in modern written Japanese, designed for the foreign student of the language who is interested in attaining and developing proficiency in reading the kind of modern Japanese that is current use in books, magazines, and newspaper in Japan.
Keywords: Japanese language; Readers